Observation of ultrasonic signal and measurement of H2 concentration from the exterior of a metal pipe. (30th August 2019) - Taskin, Mahjabin; Utsumi, Ginshiro; Kato, Yoshimine
Abstract: Concentration of H2 gas in a stainless steel (SUS) pipe is measured by using ultrasound from the exterior of a pipe without making a hole. Gas concentration is calculated by the variation of ultrasound speed detected. A sound absorbing material is put on the outer surface of the SUS pipe to reduce the ultrasonic signal noise circulating through the shell of the SUS pipe. Then it is possible to measure the gas concentration by observing the airborne signal passing through the SUS pipe. Propagation of ultrasound wave in SUS pipe is also simulated by the finite-difference-time-domain method that could explain the ultrasound propagation signals in the SUS pipe. Highlights: Airborne signal was observed by pasting sound absorbing material on the pipe surface. Gas concentration was measured using ultrasound from exterior of a metal pipe. Noise signal was canceled using two transmitters by simulation.